RESPON PERBANKAN SYARIâAH DAN LEMBAGA KEUANGAN SYARIAH DI PAMEKASAN TERHADAP PEMBUKAAN PROGRAM STUDI PERBANKAN SYARIâAH DI STAIN PAMEKASAN - Haryanto, Rudy (STAIN PAMEKASAN, 2011)
There are three focuses becoming study in this research that is: a) Response ( appresiation ) Syariah Bangking and Financial Institution of Syariah in Pamekasan, b) Expectation of Syariah Bangking and Financial Institution of SyariAh in Pamekasan to grad, c) Elementary compentence which must be had by grad. This research uses the approach qualitative trying to watch closely the response of the head Syariah Bangking and Financial Institution of Moslem law in Pamekasan to opening of Study Program of Syariâah Banking in STAIN Pamekasan. Result of this research showing that: Response of Financial Institution and Syariâah Banking in Pamekasan to opening the Study Program of Syariâah Banking in STAIN Pamekasan is very good, and they are also ready for cooperating in powering the Study Program of Syariâah Banking in STAIN Pamekasan. Expectation of Syariâah Banking and Financial Institution of Syariah in Pamekasan to grad of Study Program of Syariâah Banking in STAIN Pamekasan, that is; the grad of Study Program of Syariâah Banking STAIN Pamekasan next, absolute mastering the conception of Syariâah Banking supported with knowledge of conventional banking concept and domination of information Technology Skill. Elementary compentence which must be had by the grad of Study Program of Syariâah Banking in STAIN Pamekasan, that is; some of responders assess is competent, and some of other assess still many conventional banking payload, less payload of syariâah banking, and still less subjects which uplift the skill and practice because the next grad have to ready to work in banking area.